The vampire diaries. The complete second season [videorecording (DVD)] - Thompson, James L., III; Rodgers, Aida; Daniels, Mike, (Producer); Daniels, Mike, (Producer); Verschooris, Pascal; Tobin, J. Miller, 1961-; Dries, Caroline; Dries, Caroline; Shiban, John; Morgenstein, Leslie; Levy, Bob (Producer); Plec, Julie; et al. (Warner Bros. Entertainment, 2011)
They're back, and they're not alone. The seductive characters of The Vampire Diaries return for a stunning Season Two. This time Elena, Stefan, Damon, and the other residents of Mystic Falls are joined by sinister new blood. Released from the tomb, Katherine unleashes her personal brand of evil in a diabolical plot. The Originals, the world's oldest and most dangerous vampires, hunt for Elena, who discovers she has a terrifying connection to their world.